2013
DOI: 10.1080/03235408.2013.858879
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of some medicinal plant extracts to the potato tuber moth,Phthorimaea operculella(Lepidoptera: Gelechiidae)

Abstract: The potato tuber moth Phthorimaea operculella is a serious pest of potato both in the field and storage that makes great problem in storage. Farmers routinely rely on chemical insecticides that could be hazardous for human health and environment. Insecticide resistance of P. operculella has been reported all over the world, so botanical origin materials may serve as proper alternative materials for controlling the pest. Natural products are generally preferred because of they are less harmful to non-target org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…The insecticidal activity varied with insect stage, concentration of the oil and exposure time. Our results are in agreement with those reported by Moawad and Ebadah [2], Sharaby et al [24], Rafiee-Dastjerdi et al [40]. That essential oils and terpenes protect potato tubers against potato tuber moth infestation during storage.…”
Section: Discussionsupporting
confidence: 94%
“…The insecticidal activity varied with insect stage, concentration of the oil and exposure time. Our results are in agreement with those reported by Moawad and Ebadah [2], Sharaby et al [24], Rafiee-Dastjerdi et al [40]. That essential oils and terpenes protect potato tubers against potato tuber moth infestation during storage.…”
Section: Discussionsupporting
confidence: 94%
“…All adult insects were killed (100% mortality), when they were exposed to 3 μl/l air concentration for 48 h. The major compounds found in the essential oils of J. foetidissima have been reported previously to have a fungal growth inhibition [27], and an insecticidal activity Mortality percentages of potato tuber moth (Phthorimaea operculella) adults exposed to monoterpenoids (citronellol, nerol) vapors for different periods against T. granaruim larvae [17]. Our results are ± in agreement with results published by Tayoub et al [10], Rafiee-Dastjerdi et al [23], Sharaby et al [24], Moawad & Ebadah [30] who wrote that essential oils and their monoterpene components protect potato tubers against potato tuber moth infestation during storage.…”
Section: Discussionsupporting
confidence: 92%
“…Moawad [22] reported an ovicidal activity of essential oils extracted from margorum, cardamom, rosemary and terpintin to PTM. Rafiee-Dastjerdi et al [23] studied the insecticidal activity of the essential oil extracted from five different plant species, namely: basil, European pennyroyal, lavender, mint and savory on potato tuber moth. Sharaby et al [24] used the bulb powder of Allium cepa to dust potato tubers and found that it was highly effective in reducing of the number of eggs deposited as well as reducing adult emergence.…”
Section: Introductionmentioning
confidence: 99%
“…Lal [25] found that the leaves of Lantana aculeate provided most protection to the tubers, reducing damage than Eucalyptus globulus and Bacillus thurungiensis. It was observed that extracts of Piper nigrum and Matricaria chamomile showed high mortality, antifeeding and repellent effect on larva of PTM [7]. Similarly, Soliman [26] There are few literatures about extract of L.…”
Section: Tuber Dipping Methodsmentioning
confidence: 99%